Distance education regulatory frameworks: Readiness for openness in Southwest Pacific/South East Asia region nations - Belinda Tynan; Rosalind James (Open Praxis, 2013)
This paper reports in brief the pilot study, Distance Education Regulatory Frameworks, undertaken by the International Council for Open and Distance Education (ICDE) in 2010–2012 and the implications for openness for higher education in Southwest Pacific/South East Asia region nations. The project developed a methodological approach to identifying, accessing, collating, analysing and presenting the requested regulatory information. Here, the findings of the study are discussed in light of the theme of openness. In particular, what “open” may mean for the region; what inhibitors can be observed and what major changes might need to be considered. The discussion draws on formal and informal literature on regulatory frameworks for distance education (DE) in the Southwest Pacific/South East Asia region. Contextual information was collected about the nominated countries within the region, along with nine case studies from representative institutions whose primary focus was distance and online education.